The Economic Costs of Climate Change - Claudia Kemfert (Weekly Report, 2005)
International experts agree that the emission of greenhouse gases by mankind is rising further and further, and causing climate change. This can clearly be seen in the rise in the average global temperature and sea level. It is also evident in the increase in extreme weather events and natural catastrophes, which are causing enormous economic damage. If the global temperature changes by 1 degree Celsius economic damage of up to 2 trillion US dollars is possible in 2050. If greenhouse gas emissions are not reduced enough to prevent such a rise in temperature, altogether damage from natural catastrophes amounting to 137 billion euros could be caused in Germany by the year 2050. With optimal cooperation from the main emitters - Europe, Russia and the United States - the costs of reducing greenhouse gas emissions could be minimised. By offering emission rights for sale Russia would gain from climate policy, its participation could bring a revenue of up to 20 billion US dollars over a period of four years (2008 to 2012). So Russia is well advised to ratify the Kyoto Protocol.
Keywords: 330